Impact of end stage renal disease on the clinical outcomes of diabetics admitted for heart failure: Analysis of national inpatient sample - Muhammad Usman Almani; Yaqi Zhang; Muhammed Hamza Arshad; Muhammad Usman; Muhammad Talha Ayub (Journal of Cardiovascular and Thoracic Research, 2023)
Introduction: Patients with diabetes and heart failure (HF) can have varying outcomes depending on whether they also have End Stage Renal Disease (ESRD). This study aimed to compare the outcomes of patients with diabetes and HF with and without ESRD. Methods: Data from the National Inpatient Sample (NIS) 2016-2018 was analyzed to find hospitalizations for patients with HF as the main diagnosis and diabetes as a secondary diagnosis, with and without ESRD. Multivariable logistic and linear regression analysis was used to adjust for confounding factors. Results: In the total cohort of 12215 patients with a principal diagnosis of heart failure and secondary diagnosis of type 2 diabetes, the in-hospital mortality rate was 2.5%. Patients with ESRD had higher odds of in-hospital mortality (1.37x) compared to those without ESRD. The mean difference in length of stay was higher for patients with ESRD (0.49 days) and in total hospital charges (13360 US$). Patients with ESRD had higher odds of developing acute pulmonary edema, cardiac arrest, and requiring endotracheal intubation. However, they had lower odds of developing cardiogenic shock or requiring an intra-aortic balloon pump insertion. Conclusion: The results suggest that ESRD leads to higher in-patient mortality, length of stay, and total hospital charges for patients with diabetes admitted for HF. The lower incidence of cardiogenic shock and intra-aortic balloon pump insertion in patients with ESRD may be due to timely dialysis.